Guidance of Koran Teachers in Instilling Religious Character in Students at the Nurul Jannah Bulu TPQ Mushalla Institution, Pragaan Daya Village, Pragaan District, Sumenep Regency in 2023 - Amriyah Amriyah; Azizah Tajib (al-Afkar, Journal For Islamic Studies, 2026)
Every parent basically wants a child who is intelligent and behaves well in his life. And a child is a mandate from Allah entrusted to his parents to be raised and educated well, taught and accustomed to goodness. But in reality, not all children can go through the development process well, several factors from the family and environment can influence their development and behavior in their lives. The purpose of the study was to determine the process of guidance of religious teachers in instilling the character of religious students at the TPQ Mushalla Nurul Jannah institution and to determine the inhibiting and supporting factors of guidance of religious teachers in instilling the character of religious students at the TPQ Mushalla Nurul Jannah institution. This study uses a type of field research with a descriptive qualitative approach. Data collection techniques are carried out by means of observation, interviews and documentation with data analysis techniques, namely data reduction, data presentation and drawing conclusions. The results of the study showed that the guidance of religious teachers in instilling the religious character of students at the TPQ Mushalla Nurul Jannah institution includes 5 aspects of religiosity, namely strengthening faith in Islam with tausiyah or mau'idah hasanah (belief), reciting the Qur'an and praying in congregation (worship), being sincere in worship and khusyu' in prayer (appreciation), conducting religious studies (knowledge), and emphasizing the practice of Islamic teachings which are manifested in the form of attitudes and behavior in daily life (practice). By using the methods of exemplary behavior, habituation, advice, awareness, and punishment, and carried out directly with 2 techniques, namely individual and group. The inhibiting factors of the guidance of religious teachers in instilling the religious character of students at the TPQ Mushalla Nurul Jannah institution are the lack of support from the students' guardians, the influence of friends, laziness and lack of awareness from the students themselves. Meanwhile, the supporting factor is the proximity of the students' residence to the prayer room, so that the head of the institution and the Ustadz can monitor the activities of their students at any time.